Theatre & sexuality - Dolan, Jill 1957- (Theatre, 2010)
"This book explains the critical validity of using sexuality as a lens for examining theatres creation and reception. The book offers clear introductions to sexual identity politics, ways of reading sexuality on stage and a select history of LGBTQ theatre, including a reading of Split Britches/Bloolips production Belle Reprieve"--Provided by publisher.